Antidiabetic Effect of Young and Old Ethanolic Leaf Extracts of Vernonia amygdalina: A Comparative Study - Du-Bois Asante; Emmanuel Effah-Yeboah; Precious Barnes; Heckel Amoabeng Abban; Elvis Ofori Ameyaw; Johnson Nyarko Boampong; Eric Gyamerah Ofori; Joseph Budu Dadzie (Journal of Diabetes Research)
The young leaves of Vernonia amygdalina are often utilized as vegetable and for medicinal purpose compared to the old leaves. This study was designed to evaluate and compare the antidiabetic effects between ethanolic leaf extracts of old and young V. amygdalina on streptozotocin (STZ) induced diabetic rat for four weeks. Preliminary screening of both young and old ethanolic extracts revealed the presence of the same phytochemicals except flavonoids which was only present in the old V. amygdalina. Difference in antioxidant power between the young and old leaf extracts was statistically significant (p<0.05). Both leaf extracts produced a significant (p<0.05) antihyperglycaemic effect. Also results from treated rats revealed increasing effect in some haematological parameters. Similarly, the higher dose (300 mg/kg) of both extracts significantly (p<0.05) reduced serum ALT, AST, and ALP levels as compared to the diabetic control rats. Results also showed significant (p<0.05) decrease in LDL-C and VLDL-C in the extract-treated rats with a corresponding increase in HDL-C, as compared to the diabetic control rats. Moreover histopathological analysis revealed ameliorative effect of pathological insults induced by the STZ in the pancreas, liver, and spleen, most significantly the regeneration of the beta cells of the islets of Langerhans in treated rats.